Topological magneto-optical effects and their quantization in noncoplanar antiferromagnets - Wanxiang Feng (Nature Portfolio, 2020)
Magneto-optical effects in magnets are commonly attributed to the interplay between exchange splitting and spin-orbit coupling. Here, Feng et al. report a topological magneto-optical effect in non-coplanar antiferromagnets due to finite scalar spin chirality, without any reference to exchange splitting or spin-orbit coupling.